Program Advisory System / Choong Beng Wei - Choong, Beng Wei (2005)
The Academic Advisory System is an advisory system that uses the case based-reasoning technique in advising school leavers to courses that they should pursue in universities. The main objective of the system is to provide the advisory service of a career counsellor by recommending school leavers who want to further their tertiary education courses that are more suitable for them, based on their academic results and their personality. The system will only be able to be deployed in Malaysia as the education systems are different in each country thus making this system n t suitable to be used in other countries. The main focus group of the system would be school leavers, either from matriculation or from pre-university courses like Form Six. The system will be a web based system to facilitate the use of the system anywhere in the world and at the same time providing the advisory service at anytime of the day, unlike a human career counsellor. The case based reasoning technique is one of the reasoning methods in artificial intelligence where a problem is solved using similar solved cases in the past, by adapting the similar cases to the current problem. This technique closely mimics a human's ability to solve problems rather than the conventional machine way which is more static.